Agricultural trade policies in the Andean Group issues and options (Washington, D.C. World Bank, 1997)
"Chapter on Ecuador offers a comparison with other Andean Pact countries. Argues that Ecuador is most in need of stability and security offered by regional market access"--Handbook of Latin American Studies, v. 57.
Includes bibliographical references (p. 35).
Keywords: Produce trade -- Government policy -- Andes region; Produce trade -- Andes Region -- Statistics; Tariff on farm produce -- Andes Region